Pengaruh Penggunaan Media Mini Teater terhadap Keterampilan Komunikasi Anak Usia 5 - 6 Tahun di TK Karunia Medan Johor - Herlina Deborah Victoria; Elya Siska Anggraini; Dwi Septi Anjas Wulan; Aman Simare-mare; Roni Sinaga (Harmoni Pendidikan : Jurnal Ilmu Pendidikan, 2024)
This research aims to determine the effect of using mini theater media on the communication skills of children aged 5-6 years at Kindergarten Karunia Medan Johor. Communication skills are an important aspect of children's development, which involves the ability to speak, listen and interact effectively with other people. However, based on initial observations at Karunia Kindergarten, many children do not have good communication skills, such as lack of eye contact, unclear speech, and impoliteness when interacting. Mini theater as a learning medium has great potential to improve children's communication skills through role play that involves dialogue and interaction. This research uses an experimental method with a pre-test and post-test design in one group. The research sample was all children aged 5-6 years at Kindergarten Karunia Medan Johor, totaling 15 children. The research results show that the use of mini theater media significantly improves children's communication skills, especially in the aspects of speaking clearly, maintaining eye contact, and participating in conversations. Mini theater media has proven to be an effective tool in developing communication skills in early childhood.